The first Aleyrodidae from the Lowermost Eocene Oise amber (Hemiptera: Sternorrhyncha) - Drohojowska, Jowita; Szwedo, Jacek (Zootaxa, 2013)
The first records are provided of the family Aleyrodidae in the Lowermost Eocene amber of Oise, France. The following new taxa in the subfamily Aleurodicinae are described, figured and discussed, together with an identification key: Oisedi-cus maginus gen. et sp. n., Clodionus fizoli gen. et sp. n., Lukotekia menae gen. et sp. n. and Isaraselis cladiva gen. et sp. n. Unplaced species of Lukotekia are briefly described, and the diversity of the whiteflies from Oise amber is dis-cussed. The importance of fossils for palaeoecological and palaeoclimatological reconstruction is briefly considered.